Cover Image. (15th January 2020) - Kreszies, Tino; Eggels, Stella; Kreszies, Victoria; Osthoff, Alina; Shellakkutti, Nandhini; Baldauf, Jutta A.; Zeisler‐Diehl, Viktoria V.; Hochholdinger, Frank; Ranathunge, Kosala; Schreiber, Lukas
Abstract : The cover image is based on the Original Article Seminal roots of wild and cultivated barley differentially respond to osmotic stress in gene expression, suberization, and hydraulic conductivity by Tino Kreszies et al., https://doi.org/10.1111/pce.13719 .